Lex Cybernetika: Etika Teologis dalam Era Cyborg dan Posthumanisme - David Baluseda; Obet Nego (Sekolah Tinggi Teologi Sriwijaya, 2025)
The cyborg and posthumanism era poses significant challenges to human understanding of identity, morality, and spirituality due to the dominance of science and technology. This article examines the concept of lex cybernetica from a Christian ethical perspective, emphasizing the ethical boundaries that believers must observe in engaging with technological advancement. Through theological and ethical approaches, this study highlights the moral issues arising from innovations such as artificial intelligence, biotechnology, nanotechnology, and virtual reality, in order to help individuals remain grounded in Christian values. Employing a qualitative methodology that includes case studies, literature review, and theological descriptive analysis, the findings discuss cyborgs and posthumanism, human–technology integration, and theological reflections on humans as co-creators, ideal creations, and the relationship between soteriology and eschatology within the context of technological development.